Factors Influence Risk of Dementia in Elderly - Nanik Dwi Astutik; Sr. Felisitas (Journal of Ners and Midwifery, 2020)
The population of elderly globally is predicted continue to increase. The number of dementia cases in Indonesia reaches 1 million cases with an increase in the average life expectancy of Indonesians. WHO estimated that by 2050 cases of dementia will increase drastically, from currently around 36 million to more than 115 million. In 2011 the number of dementia cases in Indonesia showed 1 million people which will increase due to high average life expectancy continue to increase. This caused in the quality of life for the sufferer decrease which potentially became a big problem especially for developing countries that were not ready to handle large amounts of the need for treatment. Factors influence the risk of dementia were divided into 3 domain factors cardiovascular risk factors, lifestyle risk factors and other risks. The purpose of this research   analyzed factors that affect the risk of dementia among elderly in the elderly Posyandu, Tajinan Puskesmas work area Malang District. This research was cross sectional research  methods. The sample Unit in this research was elderly who actively join elderly Posyandu in Tajinan Puskesmas, Malang District. Sample count 30 using proportionate stratified random sampling technique The Data analysis used SPSS software with logistics regression analysis tests. The results of this research showed that respondents who had high blood pressure had a chance of 23.9 times higher risk of cognitive problem compared to respondents who had normal blood pressure. This research also employed research  articles, reports on research and  teaching materials as the reference. The research recommends for elderly to maintain their health status especially blood pressure and emotions to prevent the occurrence of cognitive function/dementia.